Solita Analisis Pengaruh BI rate dan Nilai Tukar Rupiah Terhadap Pendapatan Bagi Hasil Pada Bank Syariah Indonesia Periode 2021-2023 - Solita Solita (Program Studi Perbankan Syariah Jurusan Syariah, Ekonomi dan Bisnis Islam Sekolah Tinggi Agama Islam Negeri Mandailing Natal (STAIN MADINA), 2024)
This research aims to find out how much influence the BI rate and the rupiah exchange rate have on profit sharing income at Bank Syariah Indonesia for the 2021-2023 period. This research uses a quantitative approach with the type of data, namely secondary data. The population in this research is the BI rate and rupiah exchange rate reports obtained from BI reports, and monthly financial reports of Indonesian sharia banks, using purposive sampling techniques. The research results obtained were hypothesis testing (t test) for the BI Rate variable, which obtained a significant value of 0.745, which was greater than 0.05 (0.745 >0.05), while the BI Rate tcount was 0.328 and ttable was 1.692 so tcount< ttable (0.328<1.692) then it can be concluded that H1 is rejected and H0 is accepted, the rupiah exchange rate, namely the results of the hypothesis test (t test) for the rupiah exchange rate variable has a significant value of 0.000. The significant value is smaller than 0.05 (0.000 < 0.05), while the tcount value of the Rupiah Exchange Rate is 4.215 and ttable is 1.692 so tcount > ttable (4.215>1.692) so it can be concluded that H2 is accepted and H0 is rejected. Meanwhile, the BI rate and the rupiah exchange rate simultaneously influence profit sharing income as seen from the F test with a Fcount value of 13.936 > Ftable 3.285 (13.936>3.285), with a significant value of 0.00, it can be concluded that 0.00 < 0.05. Keywords: BI Rate, Rupiah Exchange Rate, Profit Sharing Income at Indonesian Sharia Banks